2010
DOI: 10.1021/ma1022555
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Responsive Properties of Poly(acrylic acid-co-acrylamide) Hydrophobic Association Hydrogels with High Mechanical Strength

Abstract: A novel type of hydrophobic association hydrogels (HA-gels) was prepared through micellar copolymerization of acrylic acid (AA), acrylamide (AAm) as basic monomers and a small amount of octylphenol polyoxyethylene ether acrylate with seven ethoxyl units (OP7-AC) as hydrophobic association monomer. The HA-gels exhibited desirable mechanical property and stably reversible phase transition between opaque and transparency. The influences of adding urea and varying AA:AAm molar ratio on the phase transition behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
89
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 120 publications
(91 citation statements)
references
References 43 publications
2
89
0
Order By: Relevance
“…Along with this, structure formation is kinetically slower than dissolution and hysteresis is often observed between heating and cooling cycles ( Figure 5) [14,36,67,68]. Both these effects have similar root causes.…”
Section: Interacting Forcesmentioning
confidence: 91%
See 3 more Smart Citations
“…Along with this, structure formation is kinetically slower than dissolution and hysteresis is often observed between heating and cooling cycles ( Figure 5) [14,36,67,68]. Both these effects have similar root causes.…”
Section: Interacting Forcesmentioning
confidence: 91%
“…The swelling and collapse of a covalently crosslinked Am-AA based hydrogel is reversible and appears complete under light transmittance observation [68], however when viewed by mass or volume, reversibility is not complete with the absolute swelling volume becoming larger after each temperature cycle. Along with this, structure formation is kinetically slower than dissolution and hysteresis is often observed between heating and cooling cycles ( Figure 5) [14,36,67,68].…”
Section: Interacting Forcesmentioning
confidence: 96%
See 2 more Smart Citations
“…As a result, the polymer exhibits a random-coil morphology. [132][133] While the preparation of macroscopic hydrogels from these materials was achieved by hydrophobic association crosslinking by Yang et al, 134 the transfer of this concept to the nanoscale was recently demonstrated by Echeverria et al by radical crosslinking copolymerization of acrylamide with acrylic acid in the presence of N,N'-methylenebis(acrylamide) in inverse emulsion. 135 Microgels prepared by this synthetic pathway represent an interesting alternative to the widely examined systems exhibiting a negative volume phase transition.…”
Section: Temperature-sensitive Microgelsmentioning
confidence: 99%